PENGARUH PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN TERHADAP SOSIAL EKONOMI RUMAH TANGGA PADA KELOMPOK SIMPAN PINJAM PEREMPUAN DI DESA ONONAMOLO II LOT KECAMATAN GUNUNGSITOLI BARAT KOTA GUNUNGSITOLI - Cardinal Pranatal Mendrofa (Welfare StatE, 2013)
Poverty is a phenomenal problem. Therefore, poverty is a topic that is very important and crucial to be completed. The phenomenon of poverty, which is most often found in rural areas, has been undertaken by the government to be resolved by establishing programs such as the National Program for Community Empowerment in Rural Areas or Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan (PNPM-MP), as a solution. This study research has the objective to determine the effect of this program on socio-economic conditions of the household in the group of women on savings and loan in Ononamolo II Lot Village, sub-district of West Gunungsitoli, Gunungsitoli. This research study considered in a descriptive study by using descriptive statistical analysis. The population in this research study were 40 women who participated in the activities savings and loan for women in Ononamolo II Lot Village, with the presentation of the data using a single table system. Methods of data collection are questionnaires, interviews, real observations, and literature study. The results showed that the influence of PNPM-MP for the socio-economic of the household in the group of women on savings and loan in Ononamolo II Lot Village, sub-district of West Gunungsitoli, Gunungsitoli, is less influential. This is caused by the lack of education that have an impact on the lack of management of the loans, the lack of participation of members of the group, and the lack of oversight by the management. Keywords : PNPM Mandiri, socio-economic, Ononamolo II Lot Village